RISK MANAGEMENT APPLICATION IN PROVIDING CREDIT RESTRUCTURING FOR THE SUPPORT OF THE HEALTHY OF BANKS BASED ON POJK NO.18/POJK.03/2016 - Theo Jornada Natanael Sianipar; Prawitra Thalib (Universitas Airlangga, 2023)
Banking institutions have a strategic role in the country's economyWork as an intermediary between parties who have excess funds with those who lack funds. In carrying out its duties, the bank is obliged to maintain public trust by implementing good governance or management and must respect the principle of bank prudence. With the emergence of the impact of Covid-19, the government together with the Financial Services Authority issued Financial Services Authority Regulation Number 11/POJK.03/2020 concerning national economic stimulus as a countercyclical to the impact of the spread of Coronavirus Disease 2019, where this policy was issued to protect customers by issuing regulations that allow provision of restructuring to affected companies. Banks in carrying out their duties must run a risk management program to minimize the occurrence of failure in one or part of a transaction or instrument finance, if the bank in carrying out its duties does not carry out risk management it can be dangerous and cause losses so that the bank must be responsible for the losses of its customers.